RANCANG BANGUN APLIKASI SISTEM PAKAR DIAGNOSIS PENYAKIT THT BERBASIS WEB DENGAN MENGGUNAKAN METODE CERTAINTY FACTOR - Wahyu Hardianto; Jusak Jusak; Sulistiowati Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
ENT (ear, nose and throat) disorders is a very common disorders in the community, based on data obtained from health department of Surabaya on January to May 2014, the ENT disorders is in rank one whose reaches 41% the number of patients in Surabaya. This resulted in the need for ENT doctors to be larger, however the number of people with the disorders ENT and the limited number of available ENT doctors in Indonesia, resulted in costs for treatment and consult with ENT doctors become more expensive.In addition to the limited number of ENT doctors in Indonesia is also still a major problem, because they had been available ENT doctor in major cities only, so ENT doctor can’t reach the communities in areas far away from urban. While the ENT disorders is a type of disorders that must be dealt with quickly and properly, so that the sufferer condition is not going worse. So it takes an expert system that reaches the general public, but can diagnose various types of ENT diseases appropriately, and provide information about treatment suggestions from the disease.Experimental results show that the web based expert system application for diagnosis ENT disorders using certainty factor method, works as expected. System can diagnose and provide information about the treatment advice of 23 ENT disorders based on 38 types of existing symptoms, the similarity results of the diagnosis by 82.6% with the diagnosis given by the an expert (ENT Doctor).